Anhedonia and the Relationship Between Other Depressive Symptoms and Aggressive Behavior. Issue 7 (April 2021) - Salem, Taban; Winer, E. Samuel; Jordan, D. Gage; Nadorff, Michael R.; Fanning, Jennifer R.; Bryant, Jessica; Berman, Mitchell E.; Veilleux, Jennifer C.
Depression has been linked to multiple forms of aggressive behavior in college students; however, it is unclear which aspects of depression explain this connection. Anhedonia, defined as the loss of interest and/or pleasure in previously enjoyed activities, may provide unique information about relationships between depression and aggression. Using cross-sectional data from two independent samples of college students ( N = 747 and N = 736 for Study 1 and Study 2, respectively), we examined whether anhedonia helped explain the relationship between broader depressive symptoms and different forms of aggressive and antisocial behavior. Anhedonia accounted for variance in both self-directed aggression and antisocial behavior independent of gender, hostility, anger, other depressive symptoms, and cognitive distortions (Study 2). In addition, there were significant indirect effects of depressive symptoms on self-directed aggression (Studies 1 and 2) and antisocial behavior (Study 2) via anhedonia. Hypotheses involving other-directed aggression received mixed support, with anhedonia atemporally associated with other-directed aggression independent of broader depressive symptoms in Study 1, but not in Study 2. The current findings suggest that anhedonia is an important individual difference that helps explain the relationship between depression and aggressive and antisocial acts and that anhedonia may be differentially associated with various types of aggressive and antisocial behavior.